Crisis management practices in the hospitality and gambling industry during COVID-19. Issue 2 (29th April 2021) - Ghaharian, Kasra; Abarbanel, Brett; Soligo, Marta; Bernhard, Bo
Abstract : Purpose: The purpose of this paper is to examine crisis management practices among gambling-related hospitality business stakeholders (GBSs) during the coronavirus disease 2019 (COVID-19) pandemic. Design/methodology/approach: An online survey was administered to a sample of GBSs resulting in 64 completed surveys. The survey explored the COVID-19 crisis using a three-phase framework: preparedness (prior experience and response plans), response (level of importance and use of crisis practices) and future (confidence in recovery, beliefs about consumer behavior and new strategies). Independent-samples t -tests were conducted to investigate the influence of preparedness variables on crisis management capabilities. Importance-Performance Analysis was used to evaluate GBSs' crisis management capabilities and identify where performance might be improved. Factor analyses were employed to explore groupings of response practices as well as future strategies. Findings: Prior experience had a significant impact on GBSs' crisis management. IPA indicated gaps between the importance GBSs assign to response practices and their corresponding level of use, specifically for those related to marketing and government. Factor analysis revealed response practices did not group according to the questionnaire's four themes, instead, three themes of marketing, efficiency and expenses were revealed. Prevention and hygiene emerged as dominant themes with respect to future strategies. Originality/value: This is a timely study that investigates crisis management among GBSs during the COVID-19 pandemic. It provides important methodological contributions as well as valuable practical considerations for gambling-related hospitality businesses.